Mycotoxins. Task 10.4 - Data analysis including the generation of European reference values (RVs) - Vasco, Elsa (2021)
Human Biomonitoring of mycotoxins in Europe: exposure determinants and geographical variability - The objective of the current study is to characterize the current exposure levels of the European population to the mycotoxins DON and FB1 and to identify exposure determinants and characterize geographical variability for these mycotoxins exposure in Europe.